1995
DOI: 10.1136/gut.37.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-hydroxytryptamine type 3 receptors in rat intestinal fluid and electrolyte secretion induced by cholera and Escherichia coli enterotoxins.

Abstract: Cholera toxin and Escherichia coli heat labile toxin (LT) induced intestinal secretion has in the past been attributed exclusively to an increase in intracellular cAMP whereas E coli heat stable toxin (ST) induced secretion is mediated through cGMP. Evidence is accumulating on the importance of 5-hydroxytryptamine (5-HT) in cholera toxin induced secretion, but its role in LT and ST is not well established. This study therefore investigated in vivo the effect of 5-HT3 receptor antagonist, granisetron, on intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…Studies with fish tetrodotoxin (TTX) showed that CT interacts with the enteric nervous system, inducing the secretion of neurohormones such as 5-hydroxytryptamine and vasoactive intestinal peptide (61,62) . LT is the major virulence factor of enterotoxigenic E. coli; it was found that LT binds to several brush-border galactoproteins only weakly recognised by CT, and it was suggested that binding of LT to this additional receptors might have a role in intestinal secretion pathophysiology (59,63) . Recent studies demonstrated that, beyond its ability to bind to different glycolipids on the surface of enterocytes, LT binds to LPS on the surface of E. coli (64) .…”
Section: Antisecretory Factor and Gut Healthmentioning
confidence: 99%
“…Studies with fish tetrodotoxin (TTX) showed that CT interacts with the enteric nervous system, inducing the secretion of neurohormones such as 5-hydroxytryptamine and vasoactive intestinal peptide (61,62) . LT is the major virulence factor of enterotoxigenic E. coli; it was found that LT binds to several brush-border galactoproteins only weakly recognised by CT, and it was suggested that binding of LT to this additional receptors might have a role in intestinal secretion pathophysiology (59,63) . Recent studies demonstrated that, beyond its ability to bind to different glycolipids on the surface of enterocytes, LT binds to LPS on the surface of E. coli (64) .…”
Section: Antisecretory Factor and Gut Healthmentioning
confidence: 99%
“…Therefore, several efforts have been made to search for promising drugs that could be used to treat cholera more efficiently. These methods include inhibitors of cholera toxin receptor binding (Pickens et al, 2004), 5-hydroxytryptamine receptor antagonists (Mourad et al, 1995;Turvill and Farthing, 1997), somatostatin receptor agonists (Farthing, 1996), enkephalinase inhibitors (Cézard et al, 2001), and CFTR inhibitors (Muanprasat et al, 2004(Muanprasat et al, , 2007. Several natural products isolated from plants have also been used as sources of pharmaceuticals and as ingredients of traditional medicines (Phillipson, 1994).…”
mentioning
confidence: 99%
“…The dose of these antagonists is capable of inhibiting cholera toxininduced secretion (7,38,39). Values are means (SD) and 95% confidence intervals (CI) in each group of animals.…”
Section: No Synthase Inhibition Vip Antagonism and 5-ht 3 And 5-ht4mentioning
confidence: 99%